2020
DOI: 10.11648/j.ajlm.20200503.13
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy History and Associated Factors Among Hawassa University Regular Undergraduate Female Students, Southern Ethiopia

Abstract: Introduction: Global incidence of pregnancies among University students is increasing; and challenging in Universities of Ethiopia. There are a few studies on pregnancy experiences among university students in Ethiopia. The finding will be used by policy makers, additive of the existing knowledge and as a reference for future researchers. Objective: To assess magnitude of pregnancy experiences and associated factors among Hawassa University regular female students from May 1-15, 2019. Methods: Institution base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…World Health Organization (WHO) recommends spacing pregnancies by at least 24 months [ 6 ]. However, unmet need for family planning is high in the postpartum period, ranging from 32 to 62% in low and middle- income countries [ 3 , 7 , 8 ]. Because of unmet need, unintended pregnancy is common in postpartum period [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…World Health Organization (WHO) recommends spacing pregnancies by at least 24 months [ 6 ]. However, unmet need for family planning is high in the postpartum period, ranging from 32 to 62% in low and middle- income countries [ 3 , 7 , 8 ]. Because of unmet need, unintended pregnancy is common in postpartum period [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,16 Despite this, there exists a notable unmet need for family planning during the postpartum period, ranging from 32 to 62% in low and middle-income countries. 9,17,18 Due to the limited acceptance of postpartum family planning (PPFP), the key factors influencing PPFP acceptance include the level of education, perinatal family planning, counseling, resumption of menstruation, breastfeeding status, return of sexual activity, concerns about side effects, and a perceived low risk of pregnancy. 19 Numerous investigations have revealed that socio-demographic factors, including women's age, marital status, educational attainment, place of residence, and religious affiliation, influence the acceptance of long-acting reversible contraception (LARC) in diverse contexts.…”
Section: Introductionmentioning
confidence: 99%